ANALISIS KUALITAS SISTEM INFORMASI PT RIWAY INTERNATIONAL TERHADAP KEPUASAN MEMBER MENGGUNAKAN METODE WEBQUAL 4.0 - Ang, Citra A; Ridho, Muhammat Rasid (LPPM Universitas Putera Batam, 2021)
Globalization also affects people's lifestyle where health is very important for everyone, so it cannot be denied that the medical world is currently one of the place that people really need in Batam City. PT. Riway International is a company that operates in the field of dietary supplements for human health. With the current condition of business competition, especially in Batam City which is so tight, PT. Riway International is one of the company that is able to survive and continue to strive to improve all aspects of the quality of the company, one of the aspect is the information system. This study aims to analyze the quality of information system such as Usability, Information Quality, Interaction Quality, Satisfaction at PT Riway International Batam branch. The technique reuse in this study is a quasi sample, namely using a population of residence in the city of Batam, we took 200 respondents as a sample. The measuring instrument use in this research is 5 points using a Likert scale. The data analysis method use is descriptive analysis, the data quality test in this studies use validity and reliability test and the influence test in this study use the analysis of the coefficient of determination (R2), while the hypothesis testing in this study use the t test and the F test with the help of software statistic SPSS 26. Based on the result of this studies indicate that the Information Quality has a positive and significant effect on member satisfaction, while Usability and Interaction Quality do not have a positive and significant effect on member satisfaction. Meanwhile, Usability, Information Quality, Interaction Quality together have a positive and significant effect on member satisfaction.